Adenanthera pavonina GALACTOMANNAN FOR CONTROLLED DELIVERY OF RUTIN - A PRELIMINARY STUDY - Karine A. Nobre; Carlos E. A. Soares; Ícaro G. P. Vieira; Raimundo R. de Almeida; Renato de A. Moreira; Tamara G. de Araújo; Maria E. N. P. Ribeiro; Nágila M. P. S. Ricardo (Química Nova)
Improving the development of modified release matrix systems strictly depends on selecting an appropriate agent capable of controlling the drug's release. In this study, Adenanthera pavonina galactomannan was investigated as a potential basis for developing a controlled release of rutin. This galactomannan was extracted, purified and characterized by GPC, NMR and FT-IR spectroscopy. The mannose/galactose ratio (M/G) of 1.46 was calculated by the relative area from signals of the anomeric region of 1H-NMR spectrum. The main chain of this galactomannan consists of β(1®4)-D-mannose and α(1®6)-D-galactose linked units (1H-decoupled 13C NMR, 13C DEPT 135º NMR and HSQC spectra). The sustained-release tablets containing rutin and galactomannan were compared with the extensively investigated hydrophilic matrix HPMC. Drug release analysis revealed similar release mechanism for both matrices. A new formulation for controlled drug delivery from water-swellable matrix systems is proposed.